International political aspects of OPEC+ activities in the context of energy diplomacy of Russia and Saudi Arabia before and after the start of the special military operation - A. Yu. Gasparyan; T. A. Melkonyan (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The growing interstate rivalry sweeps more and more areas of international relations, including energy issues. While the ‘traditional’ oil and gas exporters are trying to maintain or even strengthen their current positions, new players in the oil and gas market are trying to challenge the status quo. The changing situation on the oil market due to the ‘price war’ between the United States and OPEC countries serves as a clear manifestation of this trend and encourages the OPEC members to coordinate their policies more closely with external partners. This paper aims to identify the prerequisites and assess the dynamics of cooperation between Russia and the Kingdom of Saudi Arabia (KSA) within the OPEC+ framework. The first section of the paper examines the logic behind the OPEC+ agreement in the context of the development of energy cooperation between the Russian Federation and the KSA before the outbreak of the Ukrainian crisis. The authors note that the new format demonstrated stability within the first years of its existence and generated closer cooperation between the hydrocarbon exporting countries. The second section examines the development of OPEC+ in the face of increased geopolitical pressure from the United States and its allies. The authors conclude that the efforts of Washington and oil importing countries to undermine energy cooperation within the OPEC+ format have not succeeded, on the contrary the international stance of the group members has only strengthened. In conclusion, the authors emphasize that OPEC+ not only contributes to the stability of energy prices, but also brings tangible political benefits to its members. At the same time, according to the authors, the future of this format largely depends on the dynamics of international environment and, particularly, on the scale of the US-Russian confrontation.